A cupboard full of coats - Edwards, Yvvette (Oneworld Publications, 2011)
Fourteen years ago Jinx's mother was brutally murdered in their East London home. Since the tragedy Jinx's life has been poisoned by the part she played; paralyzed by guilt, she has cut herself off from her husband and young son. Then Lemon turns up on her doorstep. An old friend of her mother's, he wants to revisit events leading up to that terrible night. Over the course of one searing weekend they take a journey, fueled by Lemon's sumptuous cooking and intoxicating storytelling, back to memories of a childhood set ablaze with passion and violence. But as the intensity mounts and Jinx's life threatens to fall apart for a second time, she finally begins to believe that redemption may be within her grasp.--From back cover.